2014
DOI: 10.1080/21642583.2014.987480
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of optimal fractional-orderPIDcontroller using an artificial bee colony algorithm

Abstract: In this paper, the design of fractional-order PID controller is considered in order to minimize certain performance indices such as integral absolute error, integral square error and integral time absolute error. The design-construction leads to a high-dimensional, multi-modal, complex optimization problem which is difficult to solve analytically. We show that it can be solved heuristically using an artificial bee colony (ABC) algorithm, which is a recently emerged 'stochastic' technique inspired from the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 16 publications
0
33
0
3
Order By: Relevance
“…PID controller tuned at an exacting operating point will not offer a rewarding response when, there subsists divergence in the method operating series [2]. Therefore, soft computing supported PID controller tuning is extensively anticipated by the researchers throughout the previous few decades [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PID controller tuned at an exacting operating point will not offer a rewarding response when, there subsists divergence in the method operating series [2]. Therefore, soft computing supported PID controller tuning is extensively anticipated by the researchers throughout the previous few decades [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…as shown in Eqns(1) and(2)also and in Eqn(3). Linearization of the non-linear phase is performed in the , operating point.…”
mentioning
confidence: 99%
“…It was observed that POS tuned PID controller improves ride comfort and vehicle stability. Kesarkar and Selvaganesan (2015) designed fractional order PID controller using artificial bee colony algorithm with objective functions such as integral absolute error, integral square error, and integral time absolute error implemented to a multi-modal complex optimization problem. The authors observed that the results were promising as compared to the conventional PID method.…”
Section: Introductionmentioning
confidence: 99%
“…The recent developments in the field of fractional calculus have provided an opportunity to design an alternative controller with improved perspectives. The fractional calculus theory enables the inclusion of fractional powers on integral (λ) and derivative (μ) terms against the traditional integer terms, and they ensure the modelling of natural processes as more realistic (Chen, Yuan, Tian, & Ji, ; Kesarkar & Selvaganesan, ). The inclusion of additional terms λ and μ offers two extra degrees of freedom, which in turn provide higher flexibility during the design of controller.…”
Section: Introductionmentioning
confidence: 99%